Provably secure randomized AAβ cryptosystem - Asbullah, Muhammad Asyraf; Kamel Ariffin, Muhammad Rezal (Malaysian Society for Cryptology Research, 2015)
The security of a modern public key cryptosystem is usually viewed from their security goal and attack models, with the intention to come out with a provably secure cryptosystem. In this paper, we propose a randomized encryption setting algorithm based on the AAβ cryptosystem. We also present provable security elements for the randomized AAβ cryptosystem with emphasis given to the standard security against strongest attack model, namely the chosen-ciphertext attack. This randomized AAβ cryptosystem is projected in the random oracle model.